Advancing patient‐centered care for structurally vulnerable drug‐using populations: a qualitative study of the perspectives of people who use drugs regarding the potential integration of harm reduction interventions into hospitals. (8th January 2016) - McNeil, Ryan; Kerr, Thomas; Pauly, Bernie; Wood, Evan; Small, Will
Abstract: Aims: To explore the perspectives of structurally vulnerable people who use drugs (PWUD) regarding: (1) the potential integration of harm reduction interventions (e.g. supervised drug consumption services, opioid‐assisted treatment) into hospitals; and (2) the implications of these interventions for patient‐centered care, hospital outcomes and drug‐related risks and harms. Design: Semi‐structured qualitative interviews. Setting: Vancouver, Canada. Participants: Thirty structurally vulnerable PWUD who had been discharged from hospital against medical advice within the past 2 years, and hospitalized multiple times over the past 5 years. Measurements: Semi‐structured interview guide including questions to elicit perspectives on hospital‐based harm reduction interventions. Findings: Participant accounts highlighted that hospital‐based harm reduction interventions would promote patient‐centered care by: (1) prioritizing hospital care access and risk reduction over the enforcement of abstinence‐based drug policies; (2) increasing responsiveness to subjective health needs (e.g. pain and withdrawal symptoms); and (3) fostering 'culturally safe' care. Conclusions: Hospital‐based harm reduction interventions for people who use drugs, such as supervised drug consumption services and opioid‐assisted treatment, can potentially improve hospital care retention, promote patient‐centered care and reduce adverse health outcomes among people who use drugs.